Analisis Debit Tersedia pada DAS Temef dengan Menggunakan Metode NRECA, F.J. Mock dan Tangki - Krisnayanti, Denik Sri; Udiana, I Made; Chandra, Chrystin; Welkis, Davianto Frangky B. (MEDIA KOMUNIKASI TEKNIK SIPIL, 2021)
Temef Dam is located in Oenino Village Oenino District and Konbaki Village Polen District, Timor Tengah Selatan Regency which has a capacity of 45.79 millions m3. This research aimed to determine the amount of potential evapotranspiration using Penman Modification Method, the amount of dependable discharge with three methods that are NRECA, F.J. Mock, and Tank Methods, from those three methods will be selected a method that have closest characteristic of Temef Watershed, and filling timein Temef Reservoir. The maximum half monthly potential evapotranspiration in Temef Watershed using Penman Modification Method is 142.72 mm and the minimum is 71,25 mm. The average of annual discharge using NRECA Method is 249.89 m3/sec, F.J. Mock Method is 258.66 m3/sec, and Tank Method is 92.15 m3/sec. Based from three methods that have been used, Tank Method is the closest method to the characteristics of Temef Watershed, which RMSE value from Tank Method is 2.99. Filling time of Temef Reservoir to reach the planned reservoir volume in normal water year condition is three months and fifteen days and in low water year condition is six months.